Les plantes bulbeuses - Bonduel, Philippe (Larousse, 1990)
avantpropos LES PLANTES BULBEUSES LE CHOIX ET LA CULTURE DES PLANTES BULBEUSES LA MULTIPLICATION DES BULBES L’UTILISATION DES PLANTES BULBEUSES GUIDE DES PLANTES BULBEUSES Achimènes aìi: Amaryllis Anemone Apios Arisaéma Arum4 Bégonia4 Orchidee terrestre de Chine Brunsvigia Bulbocodium Caladium Calochortus Camassie Balisier de Binde Cardiocrinum Chionodoxa. Chlidanthus Colchique Commclina Corydalis Crinole Crocosmia Crocus Cyclamen Cypella Cyrtanthus Dahlia Dichelostemma Diérama Dracunculus Helléborine Érémurus Érythrinc Érythrone Eucharis Eucomis Freesia Fritillaire PerceNeige Jacinthe du Cap — Glaìeul Gloriosa Habranthus Hermodactylus Jacinthe des bois — Jacinthe Hyménocallis Iphéion Iris Ixia Ixiolirion Lapeirousia Nivéole Lis Muscari Narcisse Nectaroscordum — Nérine Nomocharis Notholirion Omithogale Oxalis Pancrais Pie ione Polianthcs Puschkinia Renoncule Rhodohypoxis Sandersonia Sauromatum Scadoxus Schizostylis Sciite Gloxinia Sparaxis Lis SaintJacques Sternbergia Tccophiléc Tigridia Tritéléia Tritonia Capucine Tulbaghia Tuiipe Veltheimia Watsonia Arum Zéphyranthe